INTERNALISASI NILAI-NILAI TAUHID PADA MATA PELAJARAN SAINS DI SDIT BUNAYYA PADANGSIDIMPUAN - Lelya Hilda (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2015)
Curriculum 2013 for SD / MI Basic Competence organization is done through an integrated approach .  Integration approach  aimed at shaping the character of the character super grateful for all that has been bestowed by Allah to develop their potential to be better . Learning science in SDIT Bunayya a thematic learning , which integrates several subjects are interconnected . With reference to the national education curriculum and the curriculum SDIT itself . Internalization of values Tauhid in science subjects can be seen in the ongoing learning process , where a teacher with a thematic system integrates the values of Tauhid in any material submitted .